PENERAPAN METODE PQ4R UNTUK MENINGKATKAN HASIL BELAJAR SANTRI PADA MATA PELAJARAN FIQIH KELAS II DI MADIN AL HIDAYAH BANGIL PASURUAN (VICRATINA, 2021)
Application PQ4R Method to improve student learning outcomes in class 2 fiqh subjects at Madin Al Hidayah Bangil. The objectives of this research are (1). To describe and analyze the application of the PQ4R method to class II fiqh subjects at Madin Al-Hidayah Bangil, (2) To analyze after applying the PQ4R method to improve learning outcomes in class II fiqh subjects at Madin Al-Hidayah Bangil. The results of this research are (1) student learning outcomes in class II fiqh subjects at Madin Al-Hidayah Bangil. The learning process is carried out in accordance with the procedures that have been prepared, because the researcher provides a learning implementation plan (RPP) and also a research instrument sheet that has been adjusted to the steps for implementing the PQ4R method. (2) The improvement of students' learning outcomes in practice questions was tested on class II students at Madrasah Madin Al-Hidayah Bangil. As for it can be seen from the application of the PQ4R method that has been applied in cycle I and cycle II, the data obtained that student scores begin to increase in the implementation of cycle 1 with a total score of 2240 and an average value of 74.6 and a total percentage of 56.6%. In the implementation of the second cycle, it was obtained that the data experienced an increase in learning outcomes that the total score reached 2560 and the average value was 85.3 and the total percentage value was 83.3%. Kata Kunci: PQ4R Method and Learning Outcomes